Urban Growth Boundaries and their Impact on Land Prices - Ball, M.; Cigdem, M.; Taylor, E.; Wood, Gavin (Pion Limited, 2014)
Undeveloped land transactions at the urban fringe of the Melbourne metropolitan area in Australia are recorded in a dataset that enables exploration of the impact of its urban growth boundary (UGB) on residential land prices. Estimation can take account of a wide range of factors, while controlling for policy anticipation effects and other potential influences on land prices. Modelling estimates indicate that land prices rose substantially inside the UGB after its enactment in 2003, but did not rise much outside of it. These results suggest that the urban growth boundary has had a significant upward effect on the trajectory of the urban region’s house prices.